HOW EASE OF USE, USEFULNESS TOWARD ATTITUDE OF SHOPPING AT ONLINE RETAIL - Ida Zuniarti; Dede Suleman; Susan Rachmawati; Sabil; Sri Rusiyati (Dinasti Publisher, 2020)
This study aims to analyze the relationship between ease of use and usefulness of shopping decisions at online retail. This study uses a sampling quota sampling technique with a survey method with a total sample of 90 respondents from the city of Jakarta with the criteria of respondents aged over 17 years and have made a purchase of fashion products online. The results of the study stated that ease of use and usefulness influence consumer attitudes. the results of this study can be a reference for further research.